(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2025)
This paper provides evidence of a positive relationship between the traded volume of derivatives in an organized derivatives market and economic growth. This finding suggests that activity in derivatives markets, both in developed economies and in the Latin American region, can contribute to an increase in Gross Domestic Product (GDP). These results are obtained through the implementation of a panel VAR model, in which Granger causality, cointegration, and stationarity are analyzed, providing evidence over both short- and long-term horizons. The findings contribute to a better understanding of the impact of the derivatives market on the real economy.